REPRESENTATION OF VALUES THROUGH POPULAR LITERATURE: A CASE STUDY ON TRANSRACIAL ADOPTION IN AMERICAN MOVIES - Novita Indriani (Universitas Gadjah Mada, 2015)
This thesis is intended to uncover values in American movies related to trans-racial adoption in American family. The movie samples in this thesis are Deep In My Heart, Losing Isaiah, Daughter From Danang and The Blind Side. This research analyzes the values taught by the adoptive parents to their adoptive children, and the ideology behind the movies. It uses the representation theory from Stuart Hall to analyze the representation of values in the movies. This research also employs the theory of ideology from Terry Eagleton to discover the ideology related to the values in the movies and the concept of identity from Browne. As a result, parents teach the same values to their children, whether they are adopted or biological. The values are freedom, equality, honesty, hard work, supporting each other and responsibility. They treat them equally just like their own children and they deserve to have a better life and better future even though they come from a different racial background. The ideology in the movies is “all men are created equal”, and identity in trans-racial adoption shows that through the values children can be anything they want to be because identity is the process that can be influenced by social institutions like family, the education system and their experience.Keywords: Representation, Transracial Adoption, Value, Ideology, Identity